High‐Definition Optophysical Image Construction Using Mosaics of Pixelated Wrinkles. Issue 24 (26th October 2020) - Kim, Kitae; Kim, Se‐Um; Choi, Subi; Heo, Kyuyoung; Ahn, Suk‐kyun; Na, Jun‐Hee
Abstract: Despite many efforts in structuring surfaces using mechanical instabilities, the practical application of these structures to advanced devices remains a challenging task due to the limited capability to control the local morphology. A platform that programs the orientation of mechanically anisotropic molecules is demonstrated; thus, the surface wrinkles, promoted by such instabilities, can be patterned in the desired manner. The optics based on a spatial light modulator assembles wrinkle pixels of a notably small dimension over a large area at fast fabrication speed. Furthermore, these pixelated wrinkles can be formed on curved geometries. The pixelated wrinkles can record images, which are naturally invisible, by mapping the gray level to the orientation of wrinkles. They can retrieve those images using the patterned optical phase retardation generated under the crossed polarizers. As a result, it is shown that the pixelated wrinkles enable new applications in optics such as image storage, informative labeling, and anti‐counterfeiting. Abstract : A platform that is capable of producing pixelated wrinkles based on programming the orientation of mechanically anisotropic molecules is proposed. The optics based on a spatial light modulator assembles pixelated wrinkles of a notably small dimension over a large area at fast fabrication speed. The patterned birefringence of pixelated wrinkles enables image storage, informative labeling, and anti‐counterfeiting.